Stabilizing self-assembled nano-objects using light-driven tetrazole chemistry - Nardi, Martina; Scherer, Torsten; Yang, Liang; Kübel, Christian; Barner-Kowollik, Christopher; Blasco, Eva (Polymer chemistry, 2021)
Herein, we present a new strategy for the stabilization of in situ self-assembled nano-objects using light-driven tetrazole ligation chemistry. Triblock copolymers consisting of poly(oligoethylene glycol methyl ether methacrylate) (POEGMA) as the first block, a central block containing UV-light reactive diaryl tetrazole and carboxylic acid functionalities, and poly(benzyl methacrylate) as the third block are prepared via polymerization-induced self-assembly (PISA). The obtained nano-objects (nanospheres, worms and vesicles morphologies) are photo-crosslinked via light-triggered nitrile imine carboxylic acid ligation (NICAL) without additional reagents. TEM and DLS analysis confirm the good stability of all the triblock copolymer morphologies in non-selective solvent after light irradiation.